Identification and adhesion profile of Lactobacillus spp. strains isolated from poultry - Rocha, Ticiana Silva [UNESP]; Baptista, Ana Angelita Sampaio [UNESP]; Donato, Tais Cremasco [UNESP]; Milbradt, Elisane Lenita [UNESP]; Okamoto, Adriano Sakai [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Sociedade Brasileira de Microbiologia, 2014)
In the aviculture industry, the use of Lactobacillus spp. as a probiotic has been shown to be frequent and satisfactory, both in improving bird production indexes and in protecting intestine against colonization by pathogenic bacteria. Adhesion is an important characteristic in selecting Lactobacillus probiotic strains since it impedes its immediate elimination to enable its beneficial action in the host. This study aimed to isolate, identify and characterize the in vitro and in vivo adhesion of Lactobacillus strains isolated from birds. The Lactobacillus spp. was identified by PCR and sequencing and the strains and its adhesion evaluated in vitro via BMM cell matrix and in vivo by inoculation in one-day-old birds. Duodenum, jejunum, ileum and cecum were collected one, four, 12 and 24 h after inoculation. The findings demonstrate greater adhesion of strains in the cecum and an important correlation between in vitro and in vivo results. It was concluded that BMM utilization represents an important technique for triage of Lactobacillus for subsequent in vivo evaluation, which was shown to be efficient in identifying bacterial adhesion to the enteric tract.
Keywords: Lactobacillus; identification; intestinal adhesion